Evolution of mutations in the ftsI gene leading to amino acid substitutions in PBP3 in Haemophilus influenzae strains under the selective pressure of ampicillin and cefuroxime - Vladislav Jakubu; Iveta Vrbova; Ibrahim Bitar; Marketa Cechova; Lucia Malisova; Helena Zemlickova (Elsevier, 2024)
Background: Aminopenicillins are recommended agents for non-invasive Haemophilus influenzae infections. One of the mechanisms of resistance to β-lactams is the alteration of the transpeptidase region of penicillin binding protein 3 (PBP3) which is caused by mutations in the ftsI gene. It was shown that exposure to beta-lactams has a stimulating effect on increase of prevalence of H. influenzae strains with the non-enzymatic mechanism of resistance. Objectives: The aim of our study was to compare the mutational potential of ampicillin and cefuroxime in H. influenzae strains, determination of minimum inhibitory concentration and the evolution of mutations over time, focusing on amino acid substitutions in PBP3. Methods: 30 days of serial passaging of strains in liquid broth containing increasing concentrations of ampicillin or cefuroxime was followed by whole-genome sequencing. Results: On average, cefuroxime increased the minimum inhibitory concentration more than ampicillin. The minimum inhibitory concentration was increased by a maximum of 32 fold. Substitutions in the PBP3 started to appear after 15 days of passaging. In PBP3, cefuroxime caused different substitutions than ampicillin. Conclusions: Our experiment observed differences in mutation selection by ampicillin and cefuroxime. Selection pressure of antibiotics in vitro generated substitutions that do not occur in clinical strains in the Czech Republic.